Eculizumab Prevents Recurrent Antiphospholipid Antibody Syndrome and Enables Successful Renal Transplantation. Issue 2 (8th January 2014) - Lonze, B. E.; Zachary, A. A.; Magro, C. M.; Desai, N. M.; Orandi, B. J.; Dagher, N. N.; Singer, A. L.; Carter‐Monroe, N.; Nazarian, S. M.; Segev, D. L.; Streiff, M. B.; Montgomery, R. A.
<x xml:space="preserve">Abstract</x> Renal transplantation in patients with antiphospholipid antibodies has historically proven challenging due to increased risk for thrombosis and allograft failure. This is especially true for patients with antiphospholipid antibody syndrome (APS) and its rare subtype, the catastrophic antiphospholipid antibody syndrome (CAPS). Since a critical mechanism of thrombosis in APS/CAPS is one mediated by complement activation, we hypothesized that preemptive treatment with the terminal complement inhibitor, eculizumab, would reduce the extent of vascular injury and thrombosis, enabling renal transplantation for patients in whom it would otherwise be contraindicated. Three patients with APS, two with a history of CAPS, were treated with continuous systemic anticoagulation together with eculizumab prior to and following live donor renal transplantation. Two patients were also sensitized to human leukocyte antigens (HLA) and required plasmapheresis for reduction of donor‐specific antibodies. After follow‐up ranging from 4 months to 4 years, all patients have functioning renal allografts. No systemic thrombotic events or early graft losses were observed. While the appropriate duration of treatment remains to be determined, this case series suggests that complement inhibitors such as eculizumab may prove to be effective in preventing the recurrence of APS after renal transplantation.